# (٢٧) ‫ﻤﺤﺎﻀﺭﺓ ﺭﻗﻡ‬

‫ﻤﺭﻜﺯ ﺘﻁﻭﻴﺭ ﺍﻝﺩﺭﺍﺴﺎﺕ ﺍﻝﻌﻠﻴﺎ ﻭ ﺍﻝﺒﺤﻭﺙ ﻓﻲ ﺍﻝﻌﻠﻭﻡ ﺍﻝﻬﻨﺩﺴﻴﺔ‬ 

٢٧: 

 ‫אوאא‬: ‫אنא‬ 
‫"! وאא‬#\$ %% −١
*‫ א‬+ ,-.‫عא‬01‫*)نא‬234‫א‬567",‫א‬8:& ‫"!אول‬#\$‫ن‬% () 
;<‫  &א‬A‫ א*אא‬+‫عא‬0B‫ن‬CD‫ذ‬FG)‫و‬.=>  )‫? و‬6Junction 90:;<% 
.;<‫א‬HIJ(<%‫و‬C5)KL‫د‬N‫مو‬GPQ3‫א‬IJ‫و‬،N S‫ א*א‬+‫عא‬01 )‫? و‬6 
.*‫ א‬+ 3 S‫*א‬X‫ د‬G4‫ =وא‬+Y4‫ א*א‬+‫א‬560B‫و‬A ;<‫א‬P)(١)TU‫وא‬
Assuming the incoming currents to be positive and the
outgoing currents negative, we have
I
1

I1 + (-I2) + (-I3) + I4 + (-I5) = 0
or

I1 + I4 - I2 - I3 - I5 = 0

or

I1 + I4 = I2 + I3 + I5

or

A

I
3

I
5

Incoming Current = Outgoing Current

We can express the above conclusion thus

ΣI=0

I
2

I
4

at any junction

(١)T" 

?686‫< و‬4‫א‬8 +‫[א‬T3 \,-.‫عא‬01‫א‬:& &% Z‫"!א‬#\$‫ن‬% ()‫و‬ 
.=>‫א‬,‫? )? و‬4‫אא‬IJ8‫א‬G_‫ <אא‬,-.‫عא‬01‫زאא‬closed mech] ^6 
:‫ن‬% <‫אא‬IJ(Y a +‫א‬2G‫وא‬

Σ IR + Σ e.m.f. = 0

round mesh 
:& +‫ عא‬7a‫א‬+) "‫)א‬Q+‫و‬ 
+:)‫א‬K+4‫א‬G_‫ א<אא‬.١ 
−:> +4‫א‬G_‫ א<אא‬.٢ 
−:6‫< و‬4‫א‬8 +‫א‬H :‫א‬96 .٣ 
+:6‫< و‬4‫א‬8 +‫א‬H :‫א‬e .٤ 

. ABCDH :‫א‬8< ^6< fTA‫א&دא‬.‫]א" א‬7;+X Z6(٢)TU‫א‬P)‫و‬

١

(٢٧) ‫ﻤﺤﺎﻀﺭﺓ ﺭﻗﻡ‬

‫ﻤﺭﻜﺯ ﺘﻁﻭﻴﺭ ﺍﻝﺩﺭﺍﺴﺎﺕ ﺍﻝﻌﻠﻴﺎ ﻭ ﺍﻝﺒﺤﻭﺙ ﻓﻲ ﺍﻝﻌﻠﻭﻡ ﺍﻝﻬﻨﺩﺴﻴﺔ‬

I1R1 is –ve (fall in potential)
I2R2 is –ve (fall in potential)
13R3 is –ve (fall in potential)
I4R4 is +ve (rise in potential)
E2 is –ve (fall in potential)
E1 is +ve (rise in potential)

A
I
4

I
1
E1

R
4

:&% Z‫"!א‬#\$‫ن‬% ]7;+‫و‬

B
R
2
E

R
1

D
I

-I1R1 - I2R2 - 13R3 + I4R4 - E2 + E1 = 0
I1R1 + I2R2 + 13R3 - I4R4 = E2 - E1

3

2

I2

R
3

C

(٢)T" 
+‫א‬H :‫א‬ 

8‫א? و‬e‫و‬C ?‫א‬96 +‫א‬H :‫_ضא‬+)‫"! وאא‬#\$ %% ]7;a 
T\$‫ل‬2A‫אمא=ض‬Y+‫א‬+)‫و‬. + 7  "‫א‬h+a9‫?  א‬\$ G6‫ن)نא=ض‬C f 
+‫ א‬f8‫و‬.‫دد‬i4‫ א‬+‫وא‬0+?4‫ א‬+‫"!وאא‬#\$ %% ]7;a5j‫و‬.*X‫ د‬G4‫א‬ 
.k ‫وא‬lZ4‫ &א‬.‫ א‬7+‫مא‬K )‫دد‬i4‫א‬  

Current Loop +‫\ <א‬T)?\$ 6<)m−٢ 
f8 0\$branch‫_ع‬T"8e‫و‬loop< fT"8 +‫ א‬7+‫א‬+)<);‫א‬HIJ8 
HIoX Z6(٣)TU‫א‬P)‫و‬.*‫" א‬X‫)א‬n<)me=%‫אم‬Y+‫א‬+)‫ن‬C& !"#\$‫ن‬%  
:& + \$ < \‫ א*א‬a56‫ א=ع‬a‫ ج‬++‫א‬5j‫و‬.<);‫א‬

(I1 - I2):,‫ )? و‬R46‫< و‬4‫א‬8 +‫א‬
(I2 – I3):,‫ )? و‬R56‫< و‬4‫א‬8 +‫א‬ 

R
1

B

A
E
1

I
1

D

R
4

R
2

R
5

I2

C

R
3

E

F

I

E
2

3

H

(٣)T" 
& ) 0_‫و‬.e\$ G4‫א‬,A‫ א\ <א‬aqm+)‫ن‬C< \‫א‬TA‫ دא‬+‫\? [א‬6 G‫وא< א‬ 
.(٣)TU‫א‬8P4‫ لא‬Z4‫א‬8< Q &‫א‬.‫*א‬X‫ د‬G6

Loop ABCDA:
٢

(٢٧) ‫ﻤﺤﺎﻀﺭﺓ ﺭﻗﻡ‬

‫ﻤﺭﻜﺯ ﺘﻁﻭﻴﺭ ﺍﻝﺩﺭﺍﺴﺎﺕ ﺍﻝﻌﻠﻴﺎ ﻭ ﺍﻝﺒﺤﻭﺙ ﻓﻲ ﺍﻝﻌﻠﻭﻡ ﺍﻝﻬﻨﺩﺴﻴﺔ‬

Starting from point A, we have
- I1 R1 – R4 (I1 – I2) + E1 = 0
Simplifying it further, we have
I1 (R1 + R4) - I2 R4 = E1

…(i)

Loop BEFCB:
Starting from point B, we have
- I2 R2 – R5 (I2 – I3) – R4 (I2 – I1) = 0
Or

I1 R4 – I2 (R2+ R4+ R5) + I3 R5 = 0

…(ii)

Loop EGHFE:
Starting from point E, we get
- I3 R3 – E2 – R5 (I3 - I2) = 0
or

I2 R5 – I3 (R3 + R5) = E2

…(iii) 

.k2Z‫*א‬X‫ د‬G4‫א‬Tf56k2Z‫ א*א‬+‫? [א‬f+)‫و‬  

Thevenin’s Theoreme=)r%−٣ 
>656‫ن‬+)s_ms&\$t_ 6[ ?f5j\$7",u%‫)א‬r‫א‬HIJ(a 
* 7" f86‫< و‬v‫و‬C\$G% 0v&‫א‬+‫ &א‬T>+6‫(و‬e=>6)\$G_‫دא‬ 
:& +  <7m A‫אא‬6‫< و‬4‫>א&وא‬4‫? [א‬f+)‫و‬.* 6‫< و‬4‫א‬ 
s_;‫א‬sf+=4‫אאא‬N,‫? و‬a>4‫א‬N0 −١ 
‫> د‬6 7+‫مא‬96s_;‫א‬s?‫א‬6‫< و‬4‫א‬t_ 6,‫? و‬a A‫אא‬6‫< و‬4‫א‬0 −٢ 
..‫א‬ 
‫אم‬Y+XX Z6(٤)TU‫א‬P)‫و‬.<G4‫אوאא‬8*‫ א‬+‫א;)]\? [א‬HIJ‫م‬Y+?a‫و‬ 
s‫אא‬P+_+)‫א‬I‫(و‬C−٤)TU‫א‬8R36‫< و‬4‫א‬8 +‫? [א‬f[ ;4‫وא‬.<);‫א‬HIJ 
8A-Bs_;‫א‬sf+=4‫א& אא‬.‫? [א‬fD‫و) &ذ‬.A-Bs_;‫א‬ 
:& +  <7m([−٤)TU‫א‬

V=drop across R2 = I R2
Where I is the circuit current when A and B are open.
I = E / (R1+ R2+r)
Then V= I R2= E R2 / (R1+ R2+r)

٣

‫ﻤﺭﻜﺯ ﺘﻁﻭﻴﺭ ﺍﻝﺩﺭﺍﺴﺎﺕ ﺍﻝﻌﻠﻴﺎ ﻭ ﺍﻝﺒﺤﻭﺙ ﻓﻲ ﺍﻝﻌﻠﻭﻡ ﺍﻝﻬﻨﺩﺴﻴﺔ‬

‫‪A‬‬

‫‪R‬‬
‫‪1‬‬

‫‪C‬‬

‫‪I‬‬

‫‪A‬‬
‫‪E‬‬

‫‪R‬‬
‫‪2‬‬

‫‪V‬‬

‫‪B‬‬

‫ﻤﺤﺎﻀﺭﺓ ﺭﻗﻡ )‪(٢٧‬‬
‫‪R‬‬
‫‪1‬‬

‫‪C‬‬

‫‪R‬‬
‫‪3‬‬

‫‪E‬‬
‫‪r‬‬

‫‪R‬‬
‫‪2‬‬

‫‪r‬‬

‫‪D‬‬

‫‪D‬‬

‫‪B‬‬

‫)ﺏ(‬

‫)ﺃ(‬

‫"‪ (٤)T‬‬
‫و) &ذ‪t_ 6[ ?fD‬א‪ <4‬و‪GA-Bs6‬א‪ G7+‬دא‪E>4‬و‪96‬א‪ 7+‬א‪ <4‬و‪6‬אא‪،r A‬‬
‫و‪HIJ8‬א\ ‪a‬نאא‪ <65 7‬و‪ +6‬ن &א‪+‬אز‪8 0\$,‬א‪.(C−٥)TU‬وא‪ <4‬و‪6‬‬
‫א‪ :& +  <7m  ?f+)x_ 4‬‬

‫])‪R = R2 (R1 + r)/ [R2 +(R1 + r‬‬
‫‪A‬‬

‫‪I‬‬

‫‪A‬‬

‫‪C‬‬
‫‪R‬‬
‫‪1‬‬

‫‪3‬‬

‫‪R‬‬

‫‪R‬‬

‫‪V‬‬
‫‪R‬‬

‫‪R‬‬
‫‪2‬‬

‫‪r‬‬

‫‪B‬‬
‫‪B‬‬

‫)ﺏ(‬

‫‪D‬‬

‫)ﺃ(‬

‫"‪(٥)T‬‬
‫و ‪T)n5j& +‬א‪s7U‬א;_‪A-Bs‬א&‪Ve=>6‬وא‪ <4‬و‪6‬אא‪ 0\$R A‬‬
‫‪8‬א‪.([−٥)TU‬و‪[ ?f5j‬א‪8 +‬א‪ <4‬و‪s  3aGR36‬א;_‪ :& + \$A-Bs‬‬

‫)‪I = V / (R + R3‬‬
‫‪−٤‬א‪sT)Q+‬د‪ +‬א&‪ 0y‬‬
‫)‪+‬א‪Y+‬אم‪HIJ‬א;)<‪Tf8‬א‪* 7U‬א‪5<G4‬א;)]א‪56T)Q+‬د‪ +‬א&‪C0y‬و‬
‫א‪.eG‬و)‪P‬א‪(C−٦)TU‬دא‪T"8‬د‪ +‬و‪  )n‬א&‪80y‬א‪.([−٦)TU‬و‪5j‬‬
‫א‪ ++‬جא‪ ?a])m52G‬و‪,‬א‪.‬א&‪56T‬אא‪sa‬و{>‪& T‬א‪2G‬א‪ +‬‬
‫‪ <6s‬و‪* 6‬א‪ +‬و‪56 x_ 6‬א|‪.0‬‬

‫‪٤‬‬

(٢٧) ‫ﻤﺤﺎﻀﺭﺓ ﺭﻗﻡ‬

‫ﻤﺭﻜﺯ ﺘﻁﻭﻴﺭ ﺍﻝﺩﺭﺍﺴﺎﺕ ﺍﻝﻌﻠﻴﺎ ﻭ ﺍﻝﺒﺤﻭﺙ ﻓﻲ ﺍﻝﻌﻠﻭﻡ ﺍﻝﻬﻨﺩﺴﻴﺔ‬

1
R

1
R

31

3

R

12

R

2

23

1

R

3

(‫)ﺃ‬

R

2
2

3

(‫)ﺏ‬ 
(٦)T"

R1 = R12 R31 /(R12 + R23 + R31)
R2 = R23 R1 2 /(R12 + R23 + R31)
And R3 =

R31 R23 /( R12 + R23 + R31)
. +‫א‬56 x_ 6‫و‬0|‫ *א‬6‫< و‬6s +‫א‬2G‫ &א‬T>{ 0\$

R12 = (R1 R2 + R2R3+ R3R1)/ R3= R1 + R2+ R1 R2 / R3
R23 = (R1 R2 + R2R3+ R3R1)/ R1= R2 + R3+ R2 R3 / R1
R31 = (R1 R2 + R2R3+ R3R1)/ R2= R1 + R3+ R1 R3 / R2 
Norton Equivalent5a%t_ 6−٥ 
& 6‫< و‬696 a>6385‫ وאאو‬t_ 6)Q+u6‫א‬Y+‫א‬5j 
:& + \$e=t_ 656uN ++‫א‬5j‫و‬.,‫אز‬+‫א‬

I = Vth / Rth
.5a%t_ 6‫و‬e=t_ 6s} +‫(א‬٧)TU‫א‬P)‫و‬

R th
I

Vth

Thevenin's Equivalent

R

Norton Equivalent

(٧)T"

٥

(٢٧) ‫ﻤﺤﺎﻀﺭﺓ ﺭﻗﻡ‬

‫ﻤﺭﻜﺯ ﺘﻁﻭﻴﺭ ﺍﻝﺩﺭﺍﺴﺎﺕ ﺍﻝﻌﻠﻴﺎ ﻭ ﺍﻝﺒﺤﻭﺙ ﻓﻲ ﺍﻝﻌﻠﻭﻡ ﺍﻝﻬﻨﺩﺴﻴﺔ‬

Example (1):
Determine the current x in the 4-ohm resistance in the circuit shown in Fig. (8(a))
below.
Solution:
The assumed distribution of current is
shown in Fig. (8(b)). Applying
Kirchhoff’s laws to different closed
loops, we get

2Ω
6A
2Ω

10V

10Ω

-2y + 10z + (x – y – 6) = 0
or

x – 3y + 10z = 6

3Ω

…(i)

1Ω

-2(y + z + 6) – 10 + 3(x – y – z –
6) –10z = 0
or

3x – 5y – 15 z = 40

(a)

…(ii)

2Ω

or

Y

8x – 4y – 3z = 48

…(iii)

Multiplying equation (i) by 5 and
equation (ii) by 3 and then
subtracting equation (ii) from
equation (i), we get

10V

10Ω

1Ω

E
(X-Y)

B

(Y+Z+6)

(Y+6)
6A

-(x – y – 6) – 3(x – y – z – 6) –
4x + 24 = 0

2Ω

A

F

Circuit EDCGE :

z

(X-Y-6)

3Ω
D (X-Y-Z-6)

X

C
4Ω

X
G
24V

-4 x + 95 z = -90
4 x – 95 z = 90

4Ω
X

24V

Circuit ABCDA :

(b)

…(iv)

Fig. (8)

Next, multiplying equation (ii) by 4 and equation (iii) by 5 and subtracting equation
(iii) from equation (ii), we get
-28 x – 45 z = -80
or 28 x + 45 z = 80

…(v)

Multiplying equation (iv) by 45 and equation (v) by 95 and adding the two, we get
: 2840 x = 11650
or 284 x = 1165
x = 1165 / 284 = 4.1 A

٦

(٢٧) ‫ﻤﺤﺎﻀﺭﺓ ﺭﻗﻡ‬

‫ﻤﺭﻜﺯ ﺘﻁﻭﻴﺭ ﺍﻝﺩﺭﺍﺴﺎﺕ ﺍﻝﻌﻠﻴﺎ ﻭ ﺍﻝﺒﺤﻭﺙ ﻓﻲ ﺍﻝﻌﻠﻭﻡ ﺍﻝﻬﻨﺩﺴﻴﺔ‬

Example (2):
Find I1, I2 and I3 in the network shown in Fig. (9), using loop-current method.
Numbers against resistances indicate their values in ohms.
10
A

B

40V

20

10

E
10V

20

I
1

10V

D

10

I2

C

F

I

3

50V

H

Fig. (9)
Solution:
Different loops would be taken one after another.
Loop ABCDA:
- 10 I1 – 20(I1 – I2) –10 = 0
or

3 I1 –2I2 = – 1

…(i)

Loop BEFCB:
40 – 20 I2+ 10 – 10 (I2 – I3) – 20(I2 – I1) = 0
or

2 I1 –5I2 + I3 = – 5

…(ii)

Loop EGHFE:
- 10 I3+50 –10(I3 – I2) – 10 = 0
or
1-

I2– 2 I3= – 4

…(iii)

Multiplying equation (ii) by 2 and adding it to equation (iii), we get
4 I1– 9 I2= – 14

…(iv)

Solving for I1 and I2 from equation (i) and (iv), we get:
I1 = 1A and

I2 = 2A

Solving these values in equation (iii), we have, I3=3A

٧

(٢٧) ‫ﻤﺤﺎﻀﺭﺓ ﺭﻗﻡ‬

‫ﻤﺭﻜﺯ ﺘﻁﻭﻴﺭ ﺍﻝﺩﺭﺍﺴﺎﺕ ﺍﻝﻌﻠﻴﺎ ﻭ ﺍﻝﺒﺤﻭﺙ ﻓﻲ ﺍﻝﻌﻠﻭﻡ ﺍﻝﻬﻨﺩﺴﻴﺔ‬

Example (3):
With reference to the network of Fig. (10), (where the number against resistances
indicate their values in ohms and the internal resistance of the battery is given 1 Ω) by
applying Thevenin’s theorem, find the following:
(i) The equivalent e.m.f. of the network when viewed from
terminals A and B.
(ii) The equivalent resistance of the network when looked into
from terminals A and B.
(iii) Current in the load resistance RL of 15Ω
Solution:
(i)

Current in the network after load resistance has been removed [Fig.
(10(b))]=24/(12+3+1)=1.5A
Then voltage across terminals AB=V=12*1.5=18V
Hence, so far as terminals A and B are concerned, the network has an e.m.f. of
18 volt (and not 24V).

(ii) There are two parallel paths between points A and B [Fig. (11(a))]. Imagine that
battery of 24V is removed but not its internal resistance. Then equivalent
resistance of the circuit as looked into from points A and B is
R=12*4/(12+4)=3 Ω
3Ω

A

C

C

A

3Ω
24V
1Ω

12 Ω

24V
1Ω

15 Ω

12 Ω

V

B
D

D

B

(a)

(b)

Fig. (10)
(iii) When load resistance of 15Ω is connected across the terminals, then the network
is reduced to the structure shown in Fig. (2.9(b)). Then
I=18/(15+3)=1A.
C

A

1

A

3Ω
1Ω

12Ω

R

18V
3Ω

15 Ω

B
D

B

(b)

(a)

Fig. (11)

٨

(٢٧) ‫ﻤﺤﺎﻀﺭﺓ ﺭﻗﻡ‬

‫ﻤﺭﻜﺯ ﺘﻁﻭﻴﺭ ﺍﻝﺩﺭﺍﺴﺎﺕ ﺍﻝﻌﻠﻴﺎ ﻭ ﺍﻝﺒﺤﻭﺙ ﻓﻲ ﺍﻝﻌﻠﻭﻡ ﺍﻝﻬﻨﺩﺴﻴﺔ‬

Example (4):
Three resistances R, 2R and 3R are connected in delta, Fig. (12(a)). Determine the
resistances for an equivalent star connection. In Fig. (13), 160 volts are applied to the
terminals AB. Determine (a) the resistance between the terminals A and B and (b) the
current.
100 Ω
1
3R

R
3

A

1

1

C

D
E

R

2

2R

3

1

R

R

60 Ω

2

160V

2

3

40 Ω
80 Ω

88 Ω

(b)

(a)

Fig. (12)

B

1

Fig. (13)
Solution:
The three resistances are joined in delta in Fig. (12(a)).
We have in Fig. (12(b))
R1 =

R x 3R /( R + 2R + 3R) = R/2

R2 =

R x 2R /6 R = R/3

R3 =

2R x 3R / 6R= R

Take the network of Fig. (13). The
three resistances of 100 Ω, 60 Ω and 40
Ω are delta connected between terminal
points C, D and E as shown in Fig.
(14(a)). They can be converted into
equivalent star connection as shown in
Fig. (14(b)).

C
60 Ω

E

C
100 Ω

40 Ω

R

D

E

(a)

60 x 100 /(60+100+40)

= 30 Ω

R2 =

100 x 40 / 200

= 20 Ω

R3 =

40 x 60 / 200

= 12 Ω

Then the network of Fig. (14) is reduced to a simple structure of Fig. (15(a)).

٩

R

R

2
D

3

(b)

Fig. (14)
R1 =

1

(٢٧) ‫ﻤﺤﺎﻀﺭﺓ ﺭﻗﻡ‬

‫ﻤﺭﻜﺯ ﺘﻁﻭﻴﺭ ﺍﻝﺩﺭﺍﺴﺎﺕ ﺍﻝﻌﻠﻴﺎ ﻭ ﺍﻝﺒﺤﻭﺙ ﻓﻲ ﺍﻝﻌﻠﻭﻡ ﺍﻝﻬﻨﺩﺴﻴﺔ‬
D

As seen, there are two parallel paths
between points S and B, one of resistance
(20 + 80)=100 Ω and the other also of (12
+ 88) = 100 Ω. Hence, equivalent
resistance between points S and B

20 Ω

A

10 Ω

1

80 Ω
S

C
12 Ω

= 100 x 100 / 200 = 50 Ω

160 V
E

The whole network is reduced to a simple
circuit of Fig. (15(b)).
(a)

(a)

88 Ω

Then resistance between points A
and B = 30 + 50 = 80 Ω.

B
1

(b)Current I = 160 / 80 = 2 A

30 Ω

(b)
160 V

50 Ω

Fig. (15) 

١٠